The book selling landscape in Tyumen region - N. P. Dvortsova; O. B. Volkomorova; E. K. Bulatova (Библиосфера)
The article presents results of studying the landscape of book selling in Tyumen region carried out in 2016 within the project «The cultural map of Russia. Literature. Reading» which was initiated by the Federal Agency on Press and Mass Communications and « Book Industry» journal in 2015. It is the first study of book trade on the whole territory of Tyumen region including its two autonomous regions (Khanty-Mansi (KhMAO) and Yamal-Nenets (YNAO) ones). The objects of research are the regional administrative centers (Tyumen, Khanty-Mansiisk, and Salekhard), cities with population over 100,000 (Surgut, Nizhnevartovsk and Nefteyugansk in KhMAO and Novyi Urengoy and Noyabrsk in YNAO, as well as the two most representative cities in the south of Tyumen region (Tobolsk and Ishim). The research methodology and techniques are based on the combination of landscape reconstruction strategies, social survey and a comparative-typological analysis. The authors study the state of traditional regional bookstores, either universal shops by their book assortment, or niche (specialized) ones, federal network shops, and Internet shops. The research revealed general well-being of book selling industry in the region alongside its negative dynamics in KhMAO and YNAO due to decline in bookshops number and total shop floor area occupied with books. Tyumen is the leader in bookselling with over 50 bookshops. The ratio of the number of Tyumen residents to a bookshop is 1:14411. In Tobolsk and Ishim the situation is different: the bookshops - residents ratio is 1:14574 and 1:16380 correspondingly. The bookselling landscape in KhMAO is more varied than that one in YNAO. Surgut is the leader of bookselling in KhMAO where there is 1 bookshop per 15847 residents. In three main cities of YNAO (Salekhard, Novyi Urengoy and Noyabrsk) the ratio of the residents per one bookshop is 1:30059. As a whole, a development tendency in the region is close interrelation of different forms of the cultural space. Such symbiosis allows saving rental payments and increasing the effectiveness of book products promotion. The most important feature of the bookselling landscape in Tyumen region is the absence of any links between the bookselling companies in thearea. Obviously, the problem of creating an integrated book environment (publishing and bookselling) remains to be solved.